What you don't know will hurt you: sexual abuse in schools - Skarbek, Denise (Rowman & Littlefield Education, 2009)
Child abuse: what is it and how does it happen? -- See no evil, hear no evil, speak no evil: not true with legislation -- Shh! the deadly silence of sexual abuse in special education -- The silent sin of sexual abuse: lessons learned from the past -- Sexual abuse prevention in schools -- Prevention curriculum -- Appendix A: federal criminal code -- Appendix B: teaching cases